Very early orthodontic treatment: when, why and how? - Ute E. M. SCHNEIDER-MOSER; Lorenz MOSER (Dental Press Editora, 2022)
ABSTRACT Introduction: Several orthodontic problems should already be treated at an early age to prevent the necessity of future complex and expensive procedures. Scientific evidence suggests that posterior crossbites, mild to moderate Class III, as well as certain Class II malocclusions, open bites and arch length discrepancies can benefit from simple, but efficient interceptive therapy. Objective: To summarize the existing evidence-based literature on early orthodontic treatment, and to illustrate its application and effectiveness by showcasing multiple clinical examples. Conclusion: Early short-term interceptive orthodontic treatment with simple appliances, in the deciduous or early mixed dentition phase, can efficiently correct certain malocclusions and help to either reduce the complexity or even avoid the necessity of complex and expensive procedures during puberty. For certain patients with significant arch length discrepancy the concept of serial extractions should be part of the orthodontic armamentarium.